Achieving high-performance PbS quantum dot solar cells by improving hole extraction through Ag doping. (April 2018) - Hu, Long; Zhang, Zhilong; Patterson, Robert J.; Hu, Yicong; Chen, Weijian; Chen, Chao; Li, Dengbing; Hu, Chao; Ge, Cong; Chen, Zihan; Yuan, Lin; Yan, Chang; et al.
Abstract: PbS quantum dot solar cells are promising candidates for low-cost and highly efficient light harvesting devices owing to their solution processability and bandgap tunability. The p-type ethanedithiol (EDT) treated PbS quantum dot film plays an important role in PbS quantum dot solar cells with an n-i-p junction device structure. However, despite their sulphur-rich surface the EDT-treated PbS quantum dot film still have a relatively low carrier concentration. Higher carrier concentrations in this layer are desirable to extend depletion regions and improve hole extraction. Also imbalances in the charge mobility between the intrinsic layer and the p-type layer may lead to charge build-up at this interface. These obstacles limit further improvement of the device performance. Herein, we utilize EDT-treated Ag-doped PbS quantum dots as a p-type layer to fabricate PbS quantum dot photovoltaic cells. The carrier carrier concentration, mobility and band extrema as well as Fermi energy levels of Ag doped PbS quantum dot film can be tailored by tuning the Ag/Pb mole ratio from 0.0% to 2.0% during fabrication. The device performance has been significantly improved from 9.1% to 10.6% power conversion efficiency largely due to improvements in carrier concentration in the PbS-EDT layer through the incorporation of silver impurities. Graphical abstract: Schematic of (a) the control device structure showing the drawbacks of a high Fermi level in the PbS-EDT hole transporting layer, specifically decreased extent of the depletion region across the PbS-PbI2 and PbS-EDT interface. (b) the target device structure with a deeper, more p-type Fermi level extending the depletion region further into the PbS-PbI2 layer. These improvements in hole extraction due to incorporation of Ag in the PbS-EDT layer results in significantly improved device performance.fx1 Highlights: Ag was successfully doped in PbS quantum dots, which could provide a path to synthesize the other nanocrystals. The physical properties such as mobility, carrier concentration and band extrema as well as Fermi energy levels were tailored via tuning the ratio of Ag/Pb. The EDT-treated Ag-doped PbS quantum dot films were utilized as a p-type layer to fabricate PbS quantum dot photovoltaic cells, which significantly improved device performance from 9.1% to 10.6% power conversion efficiency due to improved carrier diffusion and reduced Schottky barrier. These physical mechanisms were systematically investigated using techniques such as temperature-dependent J-V measurements, dark J-V characteristic analysis, and contact resistance measurements and C −2 -V measurements to provide reliable evidences to support this interpretation of the improvements to the cell efficiency.